2022
DOI: 10.21037/atm-22-3035
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone inhibits colorectal cancer epithelial-mesenchymal transition via the miR-16-5p/HMGA2/β-catenin pathway

Abstract: Background: Amentoflavone is a type of bioflavonoid that exists in many Chinese medicines and has anti-inflammatory, antioxidant, antiviral, and anticancer effects. However, the effect of amentoflavone on epithelial to mesenchymal transition (EMT) in human colorectal cancer (CRC) has not been studied. In this study, we aim to explore the effect of amentoflavone on EMT in CRC. Methods:The effects of long noncoding RNA (lncRNA) miR-16-5p on proliferation, migration, and invasion were determined by in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Furthermore, in our study, we found that miR-16-5p, miR-17-5p, miR-20a-5p, and miR-93-5p, responsible for the epithelial-mesenchymal transition (EMT) of the cell [66][67][68][69][70], were significantly directly correlated with blood serum CA125 concentration and significantly inversely correlated with PGR expression levels in tumor tissue. These elevated levels of miRNAs in tumor tissues and peripheral blood of patients with HGSOC serous ovarian cancer are consistent with literature data showing similar changes in biological samples from patients with serous ovarian tumors [16,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, in our study, we found that miR-16-5p, miR-17-5p, miR-20a-5p, and miR-93-5p, responsible for the epithelial-mesenchymal transition (EMT) of the cell [66][67][68][69][70], were significantly directly correlated with blood serum CA125 concentration and significantly inversely correlated with PGR expression levels in tumor tissue. These elevated levels of miRNAs in tumor tissues and peripheral blood of patients with HGSOC serous ovarian cancer are consistent with literature data showing similar changes in biological samples from patients with serous ovarian tumors [16,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, Kim et al [77] discovered that the amentoflavone in Selaginella tamariscina is a promising EMT inhibitor of tumor invasion and migration by inhibiting TGF-β and restoring E-cadherin expression in vitro. Additionally, amentoflavone dramatically re-duced migration, invasion, and EMT in colorectal cancer by upregulating the expression of miR-16-5p, according to recent research [78]. Six well-known miRNAs of the miR-16 family, miR-15-a/B, miR-16-5p, miR-195, miR-424, and miR-497, have been extensively studied in a variety of cancers, and they are thought to act as tumor suppressors to slow the growth of tumors [79][80][81][82][83].…”
Section: Inhibition Of Tumor Metastasis and Angiogenesismentioning
confidence: 76%
“… 16 Amentoflavone exerts antitumor effects by inhibiting colorectal cancer EMT through the miR‐16‐5p/HMGA2/β‐catenin pathway. 32 These studies provide a lot of evidence that Amentoflavone is a potentially effective multitargeting drug for the prevention and treatment of a variety of cancers. Amentoflavone has a series of molecular targets and the underlying mechanisms are mainly through regulating the expression of different genes involved in cancer cell growth, cell cycle, apoptosis, autophagy, metastasis, angiogenesis, epigenetic modification, etc.…”
Section: Discussionmentioning
confidence: 99%